Sistem Pakar Diagnosis Hama Dan Penyakit Bawang Merah Menggunakan Metode Dempster Shafer - Dasril Aldo (Computer Engineering Departement, Universitas Komputer Indonesia, 2020)
Shallot is a tuber plant commonly consumed by Indonesian people. Shallot is one of the three Allium members who are popular and have high economic value. In the cultivation process, shallots are vulnerable to pests and diseases. Some pests and diseases that can attack onion plants, namely: lalat penggorok daun, ulat bawang, trips, ulat tanah, layu fusarium, bercak ungu, antraknosa, virus mozaik bawang, bercak daun. Usually when the onion plants are attacked by pests or diseases, farmers directly provide pesticides or treatments which sometimes do not match the pests and diseases that attack. As a result, handling that is not optimal can even lead to new pests or diseases. The purpose of this study is to help farmers detect early symptoms of shallot pests and diseases so that the handling of pest and disease attacks is carried out more directed and maximally. The data processed is 10 data attacks using the Dempster Shafer method. This method processes data in the form of symptoms that produce a diagnosis in the form of shallot pests and diseases and handling steps with an accuracy rate of 95%. So this method is suitable for use in the diagnosis of shallots pests and disease. Keywords: Expert System, Dempster Shafer, Diagnosis, Shallot Pests and Disease.